Geoecological Characteristics and Comprehensive Assessment of the Effectiveness of Urban Improvement Management in a Large Siberian City - E. N. Koroleva (Управленческое консультирование)
Introduction. The issues of creating, preserving and improving the quality of green areas are relevant not only for the municipality — the city of Barnaul, but also for each urban settlement of the Russian Federation, village and settlement.Methodology. To identify numerous shortcomings in the management, a statistical analysis of the main indicators of the development of the improvement sector, the main opinions of «experts», was carried out. In order to find ways out to ensure the comfort of living for each resident of the city, a theoretical generalization is used.Results. The main geoecological characteristics of the municipality — the city of Barnaul – are described. It reflects not only the achievements of local governments in this area, but also highlights the main problem-the lack of a unified concept of landscaping. To predict the development of the city and the formation of a unified approach to landscaping, the main measures are proposed that will allow creating an up-to-date, and most importantly, allowing each resident to comfortably exist, a model for managing the field of landscaping.Analysis and discussion. The forecast estimate for the municipality — the city of Barnaul from the proposed measures for rational use of natural resources is given.Conclusions. The application of these results is not only possible, but it is also necessary to take into account the local self-government bodies when managing the geoecological processes of each city of the Russian Federation in order to achieve an optimal standard of living for the population.